Building Capacity in Institutional Research and Decision Support in Higher Education (Knowledge Studies in Higher Education,, 2018)
This book examines the relevant roles, skills and knowledge needed to build the institutional research capacity across the higher education sector globally. The information contained herein will inform IR practitioners, senior level institution officials, and higher education scholars. With a focus on building the capacity of the IR profession, this book's primary audiences include senior leaders who wish to introduce or strengthen their understanding for effective decision support and staff members who are currently in decision support units and those who wish to serve in this capacity. However, this book also offers detail on the decision support function to higher education scholars who seek to better address how data can inform policy and planning in higher education. Through a broad discussion about the roles and skills of the practitioners, this book will also enumerate the ways in which decision support practitioners can be valued contributors in shaping the future decisions and direction of specific institutions and higher education broadly.